Speed discounting and racial disparities: evidence from speeding tickets in Boston - Nejat Anbarci; Jungmin Lee (Institute for the Study of Labor (IZA), 2008)
Law enforcement officers are allowed to exercise a significant amount of street-level discretion in a variety of ways. In this paper, we focus on a particular prominent kind of discretionary behavior by traffic officers when issuing speeding tickets, speed discounting. Officers partially forgive motorists by writing a lower speed level than the speed that officers observe. Verifying the level of speed discounting by different groups of officers and motorists and ascertaining the presence of racial disparities in this lenient policing are the main objectives of this paper. We find that minority officers, particularly African-Americans, are harsher on all motorists but even harsher on minority motorists regarding speed discounting. The minority-on-minority disparity appears to be stronger in situations involving Hispanic officers, infrequently ticketing officers, male motorists, those driving old vehicles, and minority neighborhoods.
urn:nbn:de:101:1-20090107109
Keywords: J70; K42; 330; Police discretion; disparate treatment; racial bias; speeding tickets; Geschwindigkeitsbegrenzung; Strafe; Gebühr; Ethnische Diskriminierung; Polizei; Boston (Mass.)